2017
DOI: 10.1039/c7ra00232g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an inorganic polymer coagulant and coagulation behavior for humic acid/algae-polluted water treatment: polymeric zinc–ferric–silicate–sulfate coagulant

Abstract: Algae and algae organic matter (AOM) are not the sole pollutants in algae-polluted water. Other pollutants such as colloidal particles and natural organic matter should be simultaneously removed and might influence the treatment of algae and AOM. A new polymeric zinc-ferric-silicate-sulfate (PZFSiS) coagulant was prepared, and the relationship between its structure and performance in the treatment of humic acid (HA)/algae-polluted water was discussed. PZFSiS coagulants prepared under different conditions had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Figure 8B shows the IR spectra of synthetic waters (S6, S7, and S8) flocs by FC. The broad peak in all flocs at 3327 cm −1 is due to the polar interaction of Fe ions and their hydrolyzed products, which tend to form complexes with metal ions [59]. The disappearance of S-H band at 2548 cm −1 in S7 indicates the formation of covalent bonds between thiols and Zn 2+ onto the NPs surface [60].…”
Section: Characteristics Of Flocsmentioning
confidence: 97%
“…Figure 8B shows the IR spectra of synthetic waters (S6, S7, and S8) flocs by FC. The broad peak in all flocs at 3327 cm −1 is due to the polar interaction of Fe ions and their hydrolyzed products, which tend to form complexes with metal ions [59]. The disappearance of S-H band at 2548 cm −1 in S7 indicates the formation of covalent bonds between thiols and Zn 2+ onto the NPs surface [60].…”
Section: Characteristics Of Flocsmentioning
confidence: 97%
“…Coagulation is considered as an indispensable step to be adopted prior to ltration (e.g., sand ltration and membrane separation), because it allows for the effective removal of particulates and natural organic matters (NOM). 1 Particulates in source water are destabilized by the addition of positively charged coagulants, and they aggregate to larger ocs during random collision, which is usually driven by mechanical agitation. 2 The removal of NOM depends on the direct precipitation of NOM-ocs and/or adsorption onto metal hydroxide precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…33 Under this condition, coagulation is considered as an indispensable step to be adopted prior to UF to effectively remove the suspended Fe(III) oc. 34 In this study, with the effect of low-dose coagulants, the turbidity of effluent, electrical conductivity and the concentration of iron content reduced by 79.18%, 8.83% and more than 98%, respectively. The TOC was further reduced.…”
Section: Introductionmentioning
confidence: 76%
“…The combination of Fe(II)/PS and PFS was more effective than a single treatment and could compensate for the single Fe(II)/PS process by effective removal of suspended Fe(III) oc with the addition of a low-dose coagulant, which can further improve the quality of product water, mitigate pore blocking and form a cake layer. Among the selected coagulants, 34 Wu et al 56 concluded that PFS was the most effective in controlling membrane fouling. With the nal Fe(II) concentration reducing to 0.3 mg L À1 , no membrane fouling occurred.…”
Section: Resultsmentioning
confidence: 99%